Tinjauan Yuridis Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 Tentang Persyaratan Batas Usia Pencalonan Presiden Dan Wakil Presiden - Rio Subandri (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
The Constitutional Court is one of the institutions of judicial power Based on the constitution, the judiciary has the function of upholding law and justice. Law Number 24 of 2003 explains the duties and functions of the Constitutional Court is to handle constitutional matters regarding certain constitutional matters within the framework safeguard the constitution so that it is implemented responsibly in accordance with the will of the people and democratic ideals. In guarding the constitution, of course constitutional judges are needed have knowledge and expertise in state administration as well as a commitment to carry out and monitor state life in accordance with the corridors of the constitution, so that Every decision issued by the Constitutional Court is a legal product which does not go outside the corridors of the constitution, so that the constitution itself is maintained its constitutional. This research is motivated by the important role of the Court The Constitution in handing down decisions because it is in accordance with Article 10 of Law no. 24 2003 concerning the Constitutional Court, the decision of the Constitutional Court is final and has binding legal force. The general public, state officials, and all components of the nation have hopes that the judges of the Constitutional Court truly carry out the functions, duties and mandates in accordance with the Constitution, so that through Constitutional Judges who have a statesmanlike spirit the Constitutional Court can produce decisions that can provide a sense of justice in society.